KETERKAITAN AGAMA DAN NEGARA SERTA PENGGUNAAN HUKUM POSITIF YANG BERSUMBER PADA SYARIAT ISLAM - Nur Amelia; Zuhliyah Fitriani Luthfi (Jurnal Syariah Hukum Islam, 2018)
The relationship between religion and the State cannot be separated like fish and water. the second has a very close reciprocal relationship because the government is run together, based on the word of God, legal norms are determined by religious agreement even though the norm is contrary to the religious norms of the human world itself which then produces the State and religion are only seen as a fantastic realization of humans and religion is only complaints of oppressed beings. In the view of Islamic law enforcers, Islamic law is a law that must be upheld if social justice is to be achieved for all good people in Indonesia. However, if only using positive law without the existence of Islamic Shari'a will cause differences, as is known the positive law is only made by the government subject to sanctions and regulate all human behavior in association is different from Islamic law which governs all acts of mukallaf both in relation to God or fellow beings in legal theory there are differences in religious norms and legal norms different from Islamic Shari'a which does not separate the two things even positive law contains commands that are very binding and compelling, are clearly seen in terms of the source between which Islamic law and positive law are significant, namely that Islamic law is based on Allah's revelation and positive law originates in the reality of people's lives.